Response of vegetation dynamic change to multi-scale drought stress in the high-latitude Nenjiang River basin in China - Zhu, Guanglei; Zhao, Chunzi; Tong, Shouzheng; Zhu, Weihong (Frontiers in Ecology and Evolution, 2022)
Vegetation is crucial in maintaining climate stability, with its dynamic characteristics reflecting the ecological environmental quality. Recently, the continually increasing frequency and intensity of droughts has greatly changed how vegetation growth and development respond to drought. In this study, using normalized difference vegetation index (NDVI) and standardized precipitation evapotranspiration index (SPEI), we studied the response characteristics of vegetation dynamics to multi-scale drought stress (SPEI-1, SPEI-3, and SPEI-12) in the Nenjiang River basin (NRB) via Pearson correlation analysis, along with further exploration of the vegetation stability under drought. The results showed that the same period effect of drought on vegetation growth in NRB mainly occurs during the early and middle stages of vegetation growth. Furthermore, the proportion of significant positive correlation between them is 15.3–43.3%, mainly in the central and southern parts of the basin. The lagged period effect of drought on vegetation growth mainly occurred during autumn in the southeast and middle of the basin, with a significant positive correlation of 20.8%. Under drought stress, the forest vegetation stability in NRB was the highest, with the resilience of wetland and grassland vegetation being the best and worst, respectively. Our study results will not only deepen our understanding of the dynamic vegetation changes in the high-latitude semi-arid basin under global climate change, but also provide a scientific basis for the management and water resources allocation of “agriculture-wetland-forest” complex ecosystem in the future.